Suitability of excellent talent for TVET majoring in engineering - Sanusi, Amanina Binti Muhamad (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2025)
This study is to identify the suitability of the excellent talent components based on the industry's needs for more multitasking engineering graduates. Today's industry needs involve a workforce that is able to equip themselves with a wider range of skills and talents, especially in the world of digitalization. With that, there are several domains that have been identified in shaping the work talents of students. Among them are 1) relational talents; 2) the talent to influence, 3) the talent for self-improvement; 4) talent for thinking, 5) talent for digitalization technology and; 6) employability talent to ensure that TVET graduates are able to work in a high-tech environment in the future. The data of this study involved 741 respondents collected through a set of questionnaires at technical universities this study focuses on the guidelines in PPPM (PT) 2015-2025 to produce multitasking TVET graduates. The study used Win steps software and Statistical Packages for the Social Sciences. The results were to determine the usability of the items in the study, the mean score and the mean measure of domain is show that all components for each domain were appropriate. Where, 42 components for 6 domains were obtained suitable. That all 6 component is for; 1) relational talents; 2) the talent to influence, 3) the talent for self-improvement; 4) talent for thinking, 5) talent for digitalization technology and; 6) employability talent are suitable. This study prepare graduates with competent work styles to contribute the production of expert manpower in technologically advanced industrial world.